The influence of women's leadership on corporate sustainability in Indonesia - Nina Kurnia Dewi; Arif Imam Suroso; Idqan Fahmi; Rizal Syarief (Cogent Business & Management, 2023)
This article examined the influence of women's leadership on corporate sustainability by mediating business competence and organizational competence. The research method was quantitative based on positivism and hypothesis testing, combining WarpPLS and the PLS-SEM technique for multivariate analysis. The research was conducted in Indonesian State-Owned Enterprises (SOEs) using a survey, namely an online census of all female leaders at the board of directors and directors' level minus one (BoD-1) with a response rate of 73%. The characteristics of women's leadership in Indonesian SOEs tended to be visionary-type leadership compared to organic-type leadership. They were very prominent as crucial players in the organization, built a strong relationship between the leaders and staff, and could make decisions by centralizing decision-making on the leaders. The investigation's findings using the Structural Equation Model (SEM) revealed that organic leadership was significant for corporate sustainability, while visionary leadership was not significant. Business competence had a full mediation role in the influence of visionary leadership on corporate sustainability. In contrast, organizational competence only partially mediated the influence of organic leadership on corporate sustainability.
Keywords: 650; business competence; corporate sustainability; organizational competence; women’ s leadership